Electrically Responsive Surfaces: Experimental and Theoretical Investigations - Cantini, Eleonora; Wang, Xingyong; Koelsch, Patrick; Preece, Jon A; Ma, Jing; Mendes, Paula M (Accounts of chemical research, 2016)
Stimuli-responsive surfaces have sparked considerable interest in recent years, especially in view of their biomimetic nature and widespread biomedical applications. Significant efforts are continuously being directed at developing functional surfaces exhibiting specific property changes triggered by variations in electrical potential, temperature, pH and concentration, irradiation with light, or exposure to a magnetic field. In this respect, electrical stimulus offers several attractive features, including a high level of spatial and temporal controllability, rapid and reverse inducement, and noninvasiveness. In this Account, we discuss how surfaces can be designed and methodologies developed to produce electrically switchable systems, based on research by our groups. We aim to provide fundamental mechanistic and structural features of these dynamic systems, while highlighting their capabilities and potential applications. We begin by briefly describing the current state-of-the-art in integrating electroactive species on surfaces to control the immobilization of diverse biological entities. This premise leads us to portray our electrically switchable surfaces, capable of controlling nonspecific and specific biological interactions by exploiting molecular motions of surface-bound electroswitchable molecules. We demonstrate that our self-assembled monolayer-based electrically switchable surfaces can modulate the interactions of surfaces with proteins, mammalian and bacterial cells. We emphasize how these systems are ubiquitous in both switching biomolecular interactions in highly complex biological conditions while still offering antifouling properties. We also introduce how novel characterization techniques, such as surface sensitive vibrational sum-frequency generation (SFG) spectroscopy, can be used for probing the electrically switchable molecular surfaces in situ. SFG spectroscopy is a technique that not only allowed determining the structural orientation of the surface-tethered molecules under electroinduced switching, but also provided an in-depth characterization of the system reversibility. Furthermore, the unique support from molecular dynamics (MD) simulations is highlighted. MD simulations with polarizable force fields (FFs), which could give proper description of the charge polarization caused by electrical stimulus, have helped not only back many of the experimental observations, but also to rationalize the mechanism of switching behavior. More importantly, this polarizable FF-based approach can efficiently be extended to light or pH stimulated surfaces when integrated with reactive FF methods. The interplay between experimental and theoretical studies has led to a higher level of understanding of the switchable surfaces, and to a more precise interpretation and rationalization of the observed data. The perspectives on the challenges and opportunities for future progress on stimuli-responsive surfaces are also presented.